Genetic population structure of grey mackerel Scomberomorus semifasciatus in northern Australia - Broderick, D.; Ovenden, J.; Buckworth, R.; Newman, Stephen; Lester, R.; Welch, D. (Wiley-Blackwell Publishing Ltd., 2011)
This study used mtDNA sequence and microsatellite markers to elucidate the population structure of Scomberomorus semifasciatus collected from 12 widespread sampling locations in Australia. Samples (n = 544) were genotyped with nine microsatellite loci, and 353 were sequenced for the control (384 bp) and ATPase (800 bp) mtDNA gene regions. Combined interpretation of microsatellite and mtDNA data identified four genetic stocks of S. semifasciatus: Western Australia, north-west coast of the Northern Territory, Gulf of Carpentaria and the eastern coast of Queensland. Connectivity among stocks across northern Australia from the Northern Territory to the eastern coast of Queensland was high (mean F ST = 0·003 for the microsatellite data and F ST = 0·033 and 0·009 for control region and ATPase, respectively) leading to some uncertainty about stock boundaries. In contrast, there was a clear genetic break between the stock in Western Australia compared to the rest of northern Australia (mean F ST = 0·132 for the microsatellite data and F ST = 0·135 and 0·188 for control region and ATPase, respectively). This indicates a restriction to gene flow possibly associated with suboptimal habitat along the Kimberley coast (north Western Australia). The appropriate scale of management for this species corresponds to the jurisdictions of the three Australian states, except that authorities in Queensland and Northern Territory should co-ordinate the management of the Gulf of Carpentaria stock. © 2011 State of Queensland. Journal of Fish Biology © 2011 The Fisheries Society of the British Isles.